100 Micrometer bore open tubular capillary column modified with linear co-polymer chains for application in low pressure liquid chromatography. Issue 1 (20th January 2020) - Sun, Genlin; Kim, Yune Sung; Kim, Jeong Soo; Ali, Faiz; An, Hyun Joo; Cheong, Won Jo
Abstract: The performance of a 100 um i.d. open tubular column modified with linear co-polymer chains has been explored under low pressure operating conditions. A 512 mm fused-silica capillary was reacted with 3-chloropropyl isocyanate followed by sodium diethyldithiocarbamate. A copolymer layer was then immobilized on the inner surface via reversible addition-fragmentation transfer polymerization of styrene, methacrylic acid and N -phenylacrylamide. The thickness of the polymer layer was ca 1.5 µm. The column was evaluated for the separation of a mixture composed of three peptides (Trp-Gly, angiotensin I, bradykinin). The number of theoretical plates (N) as high as 72, 100 plates/column (corresponding to 140, 800/m, 7.10 µm plate height) was achieved. The column to column and day to day reproducibility of our columns was found better than 2.1%. For comparison purpose, similar chromatographic data for a selected analyte was also obtained with a commercial microcolumn of 0.5 mm id packed with a conventional C18 phase (5 µm), and 17 µm was the plate height obtained at the optimum flow rate. The van Deemter plots and kinetic plots were also obtained for comparison between our open tubular capillary column and the commercial packed column of a narrow id. Graphical Abstract: